2022
DOI: 10.3389/fmed.2022.863945
|View full text |Cite
|
Sign up to set email alerts
|

Aging of Pelvic Floor in Animal Models: A Sistematic Review of Literature on the Role of the Extracellular Matrix in the Development of Pelvic Floor Prolapse

Abstract: Pelvic organ prolapse (POP) affects many women and contributes significantly to a decrease in their quality of life causing urinary and/or fecal incontinence, sexual dysfunction and dyspareunia. To better understand POP pathophysiology, prevention and treatment, many researchers resorted to evaluating animal models. Regarding this example and because POP affects principally older women, our aim was to provide an overview of literature on the possible biomechanical changes that occur in the vaginas of animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Interobserver studies are also advisable in order to compare the agreement between different sonographers. Despite other methods to assess the biomechanical parameters of the pelvic floor muscles have been described, such a biochemical markers like elastin and collagen, ultrasound assessment seems to be the first line of study given its availability, innocuity (no histology is required) and reproducibility [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver studies are also advisable in order to compare the agreement between different sonographers. Despite other methods to assess the biomechanical parameters of the pelvic floor muscles have been described, such a biochemical markers like elastin and collagen, ultrasound assessment seems to be the first line of study given its availability, innocuity (no histology is required) and reproducibility [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency in this structure would prevent the complete closure of the urethra and could contribute to SUI ( Ashton-Miller and DeLancey, 2007 ), and several studies have shown alterations in the metabolism of collagen and elastin in periurethral connective tissues of patients affected by SUI ( Chen et al, 2006 ; Chen and Yeh, 2011 ). Aging, as well as the hormonal decay of menopause are known causes that lead to changes in the composition and structure of the ECM in the anterior wall of the vagina, resulting in mechanical alterations ( Falconer et al, 1996 ; Lin et al, 2007 ) strongly related to pelvic floor disorders ( Gardella et al, 2022 ). In pregnancy there is an intensive remodeling of the pelvic support structures to allow childbirth, and degenerative processes have been described that affect these structures as a consequence of mechanical stretching and ischemia in vaginal delivery ( Ashton-Miller and Delancey, 2009 ).…”
Section: Introductionmentioning
confidence: 99%